1987
DOI: 10.1099/00221287-133-3-701
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Chlamydia psittaci (Strain Guinea Pig Inclusion Conjunctivitis) Growth in McCoy Cells by Amino Acid Antagonism

Abstract: Chlamydiae have amino acid requirements for growth in tissue culture as defined by those amino acids whose individual omission from the growth medium prevents chlamydial multiplication. We have tested the hypothesis that this inhibition of growth arises as a result of antagonism between particular amino acids such that inhibition occurs when the concentration of one amino acid is reduced in the presence of the antagonist amino acid at high concentration. Using the Chlamydia psittaci strain guinea pig inclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…Chlamydial infection did not affect the tryptophan transport rates into polarized or nonpolarized cells, suggesting that the size of intracellular soluble tryptophan pools may be an important factor in chlamydial growth modulation. This finding agrees with that of previous studies examining nutritional requirements for chlamydial growth which indicated that intracellular amino acid pools of the host cell were sufficient for C. psittaci growth since changes in extracellular amino acid concentrations could not be detected (11).…”
Section: Discussionsupporting
confidence: 92%
“…Chlamydial infection did not affect the tryptophan transport rates into polarized or nonpolarized cells, suggesting that the size of intracellular soluble tryptophan pools may be an important factor in chlamydial growth modulation. This finding agrees with that of previous studies examining nutritional requirements for chlamydial growth which indicated that intracellular amino acid pools of the host cell were sufficient for C. psittaci growth since changes in extracellular amino acid concentrations could not be detected (11).…”
Section: Discussionsupporting
confidence: 92%
“…Transfer from overt to covert infection was a penicillin-sensitive multiple-step process dependent on host cell density and nutrition (1 15). Other factors possibly favouring persistent infection include the action of penicillin, gamma-interferon (IFNy) (12), other products of cell-mediated immunity (13), and the deprivation of the amino acids tryptophan and cysteine essential for chlamydial replication (31,32). Isolates of C. pecorum from sheep faeces seem to spontaneously produce persistent infection of cell cultures in vitro, failing to produce inclusions on serial passage in cycloheximide-treated monolayers for several weeks (1 28).…”
Section: Persistent Chlamydial Infection and Its Sign$came In Clinicamentioning
confidence: 99%
“…The organisms obtain highenergy and biosynthetic metabolites, such as ATP and amino acids (AAs), from the host cell. Earlier studies in vitro have demonstrated that the chlamydial developmental cycle is grossly disrupted by removal of all or single AAs from growth medium (1,2,11,12). In particular, abnormally large chlamydial organisms were observed inside small inclusions; these had negligible infectivity (12).…”
mentioning
confidence: 99%
“…In AA deprivation studies, media were composed of Earle's salts supplemented with vitamins to concentrations in MEM and the 13 MEM AAs (Sigma tissue-culture grade [11]) at concentrations of 100, 75, 40, 25, and 0%. Glucosedeficient medium was CMEM without glucose but including MEM nonessential AAs (a 100 M concentration of each; Gibco).…”
mentioning
confidence: 99%